HYBRID ANAEROBIC BAFFLED REACTOR FOR REMOVAL OF BOD AND PHOSPHATE CONCENTRATION IN DOMESTIC WASTEWATER - Sugito Sugito; Rhenny Ratnawati; Herlina Afiafani (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Hybrid Anaerobic Baffled Reactor (HABR) is a development technology from the Anaerobic Baffled Reactor (ABR), which was already known as a technology that is successful in treating domestic waste. Aims: The objectives of these studies were to investigate the efficiency of reducing BOD and phosphate levels in HABR with zeolite (ZE) and activated carbon (AC) media. Methodology and Results: HABR reactor made of acrylic material with a size of 90 cm x 20 cm x 30 cm. The reactor designed has 7 compartments, with details the first 5 compartments are suspended growth microorganism reactors and the next 2 compartments are attached growth microorganism reactors. Conclusion, significance, and impact of study: The result of the research showed that the efficiency of reducing BOD concentration in the reactor with ZE and AC media were 59.30% and 65.12%, respectively. The final BOD concentration in the AC reactor is 30 mg/L, this value meets the domestic wastewater quality standard required by East Java Governor Regulation Number 72 of 2013 concerning Wastewater Quality Standards for Industry and/or Other Business Activities. The final BOD concentration in the ZE reactor exceeded the required quality standard with a value of 35 mg/L. The final phosphate levels of the two reactors meet the wastewater quality standards for business and/or laundry activities with a maximum phosphate concentration of 10 mg/L. The final phosphate levels in the ZE and AC reactors were 3.74 mg/L and 8.79 mg/L, respectively. The efficiency of phosphate removal in ZE and AC reactors were 70.58% and 30.87%, respectively.